2007
DOI: 10.1152/ajpregu.00866.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of excess sympathetic activity on parasympathetic vasodilation in the rat masseter muscle

Abstract: The present study was designed to examine the effect of sympathetic tonic activity on parasympathetic vasodilation evoked by the trigeminal-mediated reflex in the masseter muscle in urethane-anesthetized rats. Sectioning of the superior cervical sympathetic trunk (CST) ipsilaterally increased the basal level of blood flow in the masseter muscle (MBF). Electrical stimulation of the peripheral cut end of the CST for 2 min using 2-ms pulses ipsilaterally decreased in a dependent manner the intensity (0.5-10 V) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…These observations suggest that the evoked MBF increases as a result of "vasodilation." Although blood vessels in the masseter muscle are innervated with sympathetic postganglionic neurons derived from the superior cervical ganglion, these neurons did not contribute to the observed MBF increases evoked by cVN stimulation, since bilateral sectioning of the CST in the present study cuts the preganglionic inputs to the superior cervical ganglion, which projects postganglionic fibers to the cranial circulation (see MATERIALS AND METHODS), and electrical stimulation of the CST consistently reduced MBF, as reported by our previous reports (14,15). Therefore, we hypothesize that the cVN stimulationinduced vasodilation in the masseter muscle is mediated by a mechanism involving a parasympathetic reflex.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These observations suggest that the evoked MBF increases as a result of "vasodilation." Although blood vessels in the masseter muscle are innervated with sympathetic postganglionic neurons derived from the superior cervical ganglion, these neurons did not contribute to the observed MBF increases evoked by cVN stimulation, since bilateral sectioning of the CST in the present study cuts the preganglionic inputs to the superior cervical ganglion, which projects postganglionic fibers to the cranial circulation (see MATERIALS AND METHODS), and electrical stimulation of the CST consistently reduced MBF, as reported by our previous reports (14,15). Therefore, we hypothesize that the cVN stimulationinduced vasodilation in the masseter muscle is mediated by a mechanism involving a parasympathetic reflex.…”
Section: Discussionsupporting
confidence: 84%
“…To examine whether capsaicin-induced changes in the parasympathetic reflex vasodilation are mediated by sympathoadrenal system, cVN stimulation was delivered before and after (10 -60 min) the intravenous administration of ␣-adrenergic blockade using phentolamine mesilate (1 mg/kg; NOVARTIS, Tokyo, Japan), or ␤-adrenergic blockade using propranolol hydrochloride (0.1 mg/kg; AstraZeneca, Osaka, Japan), in combination with capsaicin injection into the tongue. The dose of phentolamine (1 mg/kg) was chosen because it was used in our previous study for the effects of sympathetic nerve stimulation on MBF (15). The effectiveness of the blockade using propranolol was assessed by the absence of vasodilator response in response to isoproterenol hydrochloride (100 ng/kg; KOWA, Tokyo, Japan).…”
Section: Preparation Of Animalsmentioning
confidence: 99%
“…Our results, together with these of the earlier studies, suggest that both the relief of pain induced by the perfusion of metabolic byproducts and inflammatory substance due to TP compression and the increase in cardiac output due to decreased congestion induced by TP compression may result from a suppression of sympathetic nervous activity and an increase in parasympathetic nervous activity. Since an increase in parasympathetic nervous activity itself increases peripheral blood flow [35] and is one of the important factors to relief chronic pain in the muscle [19,[35][36][37], the increase in parasympathetic nervous activity induced by the above peripheral mechanisms may further decrease chronic pain or muscle fatigue. Fig.…”
Section: Physiological Effects Of Tp Compressionmentioning
confidence: 99%
“…It has been reported that masseter muscle activity is closely related to changes in ANS activity. Sympathetic nerves derived from the superior cervical sympathetic trunk (CST) that supplies blood vessels in the oro‐facial area have been reported to induce vasoconstrictor responses in the masseter muscles of a number of animal species . Additionally, sympathetic nerves from the CST have been reported to interact with parasympathetic nerves in the regulation of blood flow to oro‐facial tissues in cats and dog .…”
Section: Discussionmentioning
confidence: 99%